The constitutional conflict about confidence to the Government of the Russian Federation in the context of constitutional reform 2020 - I. A. Tretyak (Правоприменение, 2021)
The subject. The article is devoted to constitutional conflict about distrust to the Government of the Russian Federation and constitutional norms that regulated such conflict and were changed during the constitutional reform in 2020. The author analyzes such transformation in legal regulation and try to find causes for this changes. And also the author provides a constitutional-conflict diagnostic of new constitutional norms to identify conflictogens.Purposes of the paper are to find a legal reasons for transformation of constitutional norms about distrust to the Russian Government and to prevent an appearance in future long term of serious constitutional conflict by finding its conflictogens.The methodology of the study includes a new methodology of a constitutional legal science – constitutional-conflict diagnostic. The constitutional-conflict diagnostic is a system of consistently applied scientific methods, legal principles and presumptions aimed at obtaining information about the constitutional conflict and the constitutional-legal methods of its prevention and resolution. The constitutional-conflict diagnostic includes group of methods: dialectical and systemic methods, as well as structural and functional method; a group of private-scientific methods (historical, methods of formal logic: analysis, comparison). The formal-legal, comparative legal methods and a method of modeling of legal consequences are also used.The main results and scope of their application. The constitutional reform of 2020 year complicated the procedure for resolving the constitutional conflict of trust to the government and introduced a subject-status misbalance in part 4 of Article 117 of the Russian Constitution, expressed in the unmotivated and unjustified possibility of the president to had no activities for resolving such conflict.Legal modeling of the simultaneous implementation of the provisions of parts 3 and 4 of Article 117 of the Russian Constitution revealed the possibility of alternating procedures for expressing trust and denying in confidence to the government, which was absent before the constitutional reform.From a formal legal point of view and a conflictological approach, the amendments to Part 4 of Article 117 of the Constitution of the Russian Federation cannot be explained, and they are a certain «opportunistic maneuver» to the Russian Parliament.